Edukasi Personal Hygiene Saat Menstruasi pada Remaja di Desa Bangun Rejo Kecamatan Tanjung Morawa Tahun 2024 - Sri Rezeki; Erin Padilla Siregar; Astaria Br Ginting; Amellia Erawaty Siregar; Eka Purnamasari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Background: Menstruation is the discharge of blood from the genitals. At the time of menstruation, the blood vessels in the uterus are very susceptible to infection. In areas that are hot enough to make the body sweat, this sweat increases the body's moisture levels, especially in the closed and multiplied sexual and reproductive organs. Purpose: For this reason, this community service activity aims to socialize personal hygiene education during menstruation. Method: This community service activity uses the lecture method, and question and answer. The lecture method is carried out by delivering material about personal hygiene during menstruation. Meanwhile, the question and answer method is carried out by asking participants about the material that has been presented. Results: The results of this community service activity were obtained that participants were able to understand and apply the material that had been delivered. Conclusion: Based on the community service activities that have been carried out, many of the participants enthusiastically received the entire series of events ranging from material presentations to question and answer interactions.